2017
DOI: 10.1074/jbc.m116.750323
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation of Full-length Immunoglobulin Light Chains from Systemic Light Chain Amyloidosis (AL) Patients Is Remodeled by Epigallocatechin-3-gallate

Abstract: Edited by Paul E. FraserIntervention into amyloid deposition with anti-amyloid agents like the polyphenol epigallocatechin-3-gallate (EGCG) is emerging as an experimental secondary treatment strategy in systemic light chain amyloidosis (AL). In both AL and multiple myeloma (MM), soluble immunoglobulin light chains (LC) are produced by clonal plasma cells, but only in AL do they form amyloid deposits in vivo. We investigated the amyloid formation of patient-derived LC and their susceptibility to EGCG in vitro t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
65
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(68 citation statements)
references
References 91 publications
(104 reference statements)
3
65
0
Order By: Relevance
“…1C & D), without significant differences between BJP from MM or AL patients belonging to the same isotype. We confirmed that the 7 BJPs studied did not refold reversibly, in agreement with previous reports from our laboratory and others [711]. …”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…1C & D), without significant differences between BJP from MM or AL patients belonging to the same isotype. We confirmed that the 7 BJPs studied did not refold reversibly, in agreement with previous reports from our laboratory and others [711]. …”
Section: Resultssupporting
confidence: 93%
“…Bence Jones proteins from patients with AL amyloidosis or MM have been compared for their thermodynamic stability. Consistent results from these comparative studies have indicated that the former are less thermodynamically stable than MM BJPs from the same or similar germline sequence with a high level of sequence identity [7, 9, 11]. One important characteristic of the thermodynamic properties of BJPs is that these proteins do not refold reversibly, in contrast to the reversible behavior observed for immunoglobulin light chain variable domains (V L ) from AL amyloidosis proteins (for a review, please see [2]).…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations